2008
DOI: 10.3923/pjbs.2008.1646.1649
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Status of Bilirubin and Uric Acid in Patients Diagnosed with Plasmodium falciparum Malaria in Douala

Abstract: Oxidative stress and changes in antioxidant status have been implicated in the pathogenesis of malaria. To assess the antioxidant level ofbilirubin and uric acid associated with falciparum malaria infection, 60 untreated patients (30 men and 30 women) in Douala, Cameroon were screened for the study. Sixty five healthy individuals (29 men and 36 women) were used as controls. Total and conjugated bilirubin were calculated using Jendrassik-Grof method while uric acid was determined using Barham-Trinder method. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Bertrand et al . [33] describe a weak correlation (r = 0.06, p>0.05) in a group of 60 Cameroonian adults with UM. In comparing groups of Nigerian children with asymptomatic parasitemia, UM and severe malaria, Iwalokun et al [35] showed that the association between UA levels and parasite density gets stronger with disease severity; however, this correlation (r = 0.61, p<0.05) was significant only in the group of severe cases.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Bertrand et al . [33] describe a weak correlation (r = 0.06, p>0.05) in a group of 60 Cameroonian adults with UM. In comparing groups of Nigerian children with asymptomatic parasitemia, UM and severe malaria, Iwalokun et al [35] showed that the association between UA levels and parasite density gets stronger with disease severity; however, this correlation (r = 0.61, p<0.05) was significant only in the group of severe cases.…”
Section: Discussionmentioning
confidence: 78%
“…Before making these correlations, we confirmed that the cytokines we measured increase with disease severity, thus implicating them in the pathogenesis of severe malaria in our Malian study population. Previous studies that measured UA levels in patients with malaria tested the hypothesis that UA is an indirect marker of oxidative stress [33][35]. This is because the formation of UA from hypoxanthine and xanthine generates ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of plasma uricase activity may therefore contribute to malaria inflammation, as humans would have difficulty eliminating highly inflammatory uric acid precipitates released by ruptured Plasmodium -infected erythrocytes. Indeed, elevated plasma urate levels were found in Plasmodium infections in mice [55] and in humans, which correlate with disease severity in P. falciparum [25][27] and with parasitemia in P. vivax [28]. In addition, a correlation between uric acid plasma levels and inflammatory cytokines in children infected with P. falciparum in Mali was found [56].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress results from increased production of oxidants, reduced level of antioxidants or a combination of both [15]. Several studies have demonstrated that the issue of oxidative stress and antioxidants is involved in the pathogenesis of various parasitic diseases and inflammatory events [25,26]. Malondialdehyde (MDA), a marker of lipid peroxidation; a non-enzymatic antioxidant, glutathione, and enzymatic antioxidants glutathione peroxidase and superoxide dismutase have been determined in patients with hydatid cyst.…”
Section: Discussionmentioning
confidence: 99%